THE ROLE OF BAITUL MAAL WA TAMWIL TUNAS HARAPAN SYANTARA IN THE MANAGEMENT OF CLEAN WATER FACILITIES IN PESANGGRAHAN VILLAGE, EAST LOMBOK - Sarni, Sarni; Rachmad, Dedy; Nurrachmi, Rininta (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This research departs from the problem of managing clean water sources in Pesanggrahan Village, East Lombok which was carried out by Baitul Maal wa Tamwil Tunas Harapan Syantara. In conducting research, the study used qualitative research based on interviews, documentation and questionnaires as primary data in this research. In the next stage, the study analyzes the data using management theory and SWOT to look at planning, organizing, implementing, controlling models and the problems faced. After going through a long academic research process, the result indicates that the value of strengths-weakness (2.53-0.58): 2 = 0.98, while opportunities (1.50) – Threats (1.14): 2 = 0.18. The finding also indicates that the SWOT analysis quadrant graphic, the position of clean water source management is in quadrant I, which means it is good for the continuation of clean water management in Pesanggrahan Village. The next strategy that must be carried out is promotion, using advertising, sales promotion, personal selling, direct marketing and public relations.